2019
DOI: 10.1007/s10701-019-00292-w
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Manifolds as Basic Objects of General Relativity

Abstract: In this paper non-Hausdorff manifolds as potential basic objects of General Relativity are investigated. One can distinguish four stages of identifying an appropriate mathematical structure to describe physical systems: kinematic, dynamical, physical reasonability, and empirical. The thesis of this paper is that in the context of General Relativity, non-Hausdorff manifolds pass the first two stages, as they enable one to define the basic notions of differential geometry needed to pose the problem of the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Such a mechanism could potentially make use of the Everett ("many-worlds") interpretation of quantum mechanics [23], and indeed this interpretation has been investigated in the context of time travel [24,25]. Classically, non-Hausdorff manifolds [10,26,27,28,29] were suggested as a possible mathematical model for branching spacetimes. However, in both cases, no concrete mechanism has been suggested so far.…”
Section: Resolving the Paradoxes Using Multiple Historiesmentioning
confidence: 99%
“…Such a mechanism could potentially make use of the Everett ("many-worlds") interpretation of quantum mechanics [23], and indeed this interpretation has been investigated in the context of time travel [24,25]. Classically, non-Hausdorff manifolds [10,26,27,28,29] were suggested as a possible mathematical model for branching spacetimes. However, in both cases, no concrete mechanism has been suggested so far.…”
Section: Resolving the Paradoxes Using Multiple Historiesmentioning
confidence: 99%
“…This requires the addition of just a single extra axiom to the basis of common BST structures. 9 As originally described by Belnap [1], the theory posits the axioms of a common BST structure together with the so-called prior choice principle, which we will denote PCP 92 to indicate its historical origin. Basically, PCP 92 requires that whenever an event e belongs to one history h 1 but not to another history h 2 , these two histories split at a choice point c in the past of e:…”
Section: Branching Via the Prior Choice Principle Of Bst 92mentioning
confidence: 99%
“…However, there have been attempts to relax the Hausdorff property, motivated by particular candidates for space-time. It can also be argued that the Hausdorff property is not needed in General Relativity and can be abandoned at a small price [9]. Finally, there is a method of gluing (Hausdorff) differential manifolds into a larger structure, a so-call generalized manifold, that is not Haudorff.…”
Section: The Diamond Topology In Bst Nfmentioning
confidence: 99%
“…Recently, Placek [43] developed a detailed theory of branching spacetime which employs non-Hausdorff (but locally Euclidean) manifolds in order to take multiple histories into account, although he did not discuss time travel paradoxes in this context. Luc [44] (see also [45] with Placek) discussed the issue of non-Hausdorff manifolds and concluded that they can, in fact, be used as fundamental mathematical objects describing spacetime in general relativity. The basic notion of using such manifolds to describe branching universes with multiple timelines seems reasonable, but there are many conceptual and mathematical issues which need to be resolved first.…”
Section: Non-hausdorff Manifoldsmentioning
confidence: 99%
“…Here λ is an affine parameter 44 along the null geodesic. The ANEC is the weakest energy condition we have -but unfortunately, even this condition is violated in some cases.…”
Section: The Averaged Energy Conditionsmentioning
confidence: 99%